Modified cellulose, preparation method thereof and modified cellulose composite material

Modified cellulose was prepared by performing ionic liquid cosolvent pretreatment, oxidation and grafting reactions on cellulose, which solved the problem of cellulose being difficult to thermoplastic processing and insufficient antibacterial performance, and achieved thermoplastic processing and good antibacterial effects.

CN119775444AInactive Publication Date: 2025-04-08TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202510105470.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Cellulose is difficult to thermoplastic processing, and its antibacterial properties are insufficient, which causes the problem of easy loss of antibacterial agents.

Method used

By mixing pulp cellulose with ionic liquid co-solvent for pretreatment, regenerated cellulose is obtained, then oxidized with sodium periodate, and then grafted with amino cationic antibacterial agent to prepare modified cellulose with thermoplasticity and antibacterial properties.

Benefits of technology

The thermoplastic processing of cellulose is realized and its antibacterial properties are significantly improved. It can be plasticized at 200°C, and has good antibacterial activity against E. coli and Staphylococcus aureus.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775444A_ABST
    Figure CN119775444A_ABST
Patent Text Reader

Abstract

The invention provides modified cellulose, a preparation method thereof and a modified cellulose composite material, and relates to the technical field of high polymer materials. According to the method, the cellulose is subjected to dissolution regeneration pretreatment by using the ionic liquid cosolvent, so that the capability of oxidizing the cellulose is improved, and the time required for oxidizing the cellulose is shortened; then sodium periodate is adopted to oxidize hydroxyl of a cellulose glucose unit into an aldehyde group, and the aldehyde group and an amino cation antibacterial agent are subjected to a Schiff base reaction, so that an antibacterial group is successfully grafted, and the modified cellulose has a relatively strong antibacterial property; after the regenerated cellulose is selectively oxidized by the sodium periodate and is grafted and modified by the amino cationic antibacterial agent, the hydrogen bond structure of the regenerated cellulose is destroyed, so that the glass-transition temperature of the cellulose material is greatly reduced, the modified cellulose material has thermoplasticity, and even plastic processing can be realized under the condition that a plasticizer and thermoplastic plastic are not added.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to modified cellulose and a preparation method thereof and a modified cellulose composite material. Background Art

[0002] The main source of cellulose is plants, which can be regenerated through planting. Cellulose can be gradually degraded by microorganisms and eventually decomposed into carbon dioxide and water. It is an environmentally friendly material that meets the requirements of sustainable development. Although cellulose is a renewable and degradable green resource, it is difficult to perform thermoplastic processing, which is very important for converting this biomass raw material into various products.

[0003] Cellulose molecular chains are rich in hydroxyl groups, which form a complex and strong hydrogen bond network, making cellulose unable to flow at high temperatures. It also undergoes thermal decomposition below the melting temperature, making it difficult to perform thermoplastic processing. Plastic processing can be achieved by destroying the hydrogen bonds between cellulose chains under high energy and mechanical force, but this method has harsh processing conditions and high energy consumption, making it difficult to achieve large-scale production. The addition of plasticizers (water, ionic liquids, low eutectic solvents (DES) etc.) can effectively weaken the hydrogen bond interactions between cellulose molecular chains, thereby enabling thermoplastic processing of cellulose. However, this also brings about many disadvantages such as decreased mechanical properties, cost and safety.

[0004] In addition, the basic structural unit of cellulose is glucose, and bacteria on the surface are very likely to proliferate during use and storage, which has a negative impact on the material itself and consumers. Currently, adding antimicrobial agents to cellulose fibers is the main method to improve the antimicrobial properties of cellulose, but in this method, the interaction between cellulose and antimicrobial agents is mainly van der Waals force, and the interaction between cellulose and antimicrobial agents is weak, and antimicrobial agents are easy to lose.

[0005] Therefore, how to improve cellulose so that it has both thermoplastic and antibacterial properties has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0006] The purpose of the present invention is to provide a modified cellulose and a preparation method thereof and a modified cellulose composite material. The modified cellulose provided by the present invention has both thermoplasticity and antibacterial properties, and the obtained modified cellulose composite material can be subjected to multiple thermoplastic processing.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing modified cellulose, comprising the following steps:

[0009] (1) mixing pulp cellulose and ionic liquid co-solvent and then pretreating them to obtain regenerated cellulose;

[0010] (2) mixing the regenerated cellulose obtained in step (1) with a first solvent and sodium periodate and subjecting the mixture to an oxidation reaction to obtain oxidized cellulose;

[0011] (3) The oxidized cellulose obtained in step (2) is mixed with a second solvent and an amino cationic antibacterial agent and then subjected to a grafting reaction to obtain modified cellulose.

[0012] Preferably, the pretreatment temperature in step (1) is 50-90° C., and the pretreatment time is 1-2 h.

[0013] Preferably, the ionic liquid co-solvent in step (1) comprises an ionic liquid and dimethyl sulfoxide, and the mass ratio of the ionic liquid to dimethyl sulfoxide is (70-90):(10-30).

[0014] Preferably, the ionic liquid is one or more of 1-ethyl-3-methylimidazolium acetate, 1-allyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium chloride and N,N-dimethylimidazolium acetate.

[0015] Preferably, after the pretreatment in step (1) is completed, the mixed liquid obtained by the pretreatment is mixed with water and then solid-liquid separation is performed to obtain regenerated cellulose.

[0016] Preferably, in step (2), the first solvent is a mixed solvent of isopropanol and water, and the volume ratio of isopropanol to water is (0.06-0.12):1.

[0017] Preferably, the pH value of the grafting reaction in step (3) is 10-11.

[0018] Preferably, the amino cationic antibacterial agent in step (3) is one or more of polyhexamethyleneguanidine hydrochloride, polyhexamethylene biguanide hydrochloride and quaternary ammonium salt.

[0019] The present invention also provides modified cellulose prepared by the preparation method described in the above technical solution.

[0020] The present invention also provides a modified cellulose composite material, which comprises the following components, measured by weight: 50 to 100 parts of modified cellulose, 0 to 10 parts of plasticizer, 0 to 50 parts of degradable synthetic polymer and 0.1 to 0.3 parts of antioxidant, wherein the modified cellulose is the modified cellulose described in the above technical solution.

[0021] The invention provides a method for preparing modified cellulose, comprising the following steps: mixing pulp cellulose and an ionic liquid co-solvent and then performing pretreatment to obtain regenerated cellulose; mixing the regenerated cellulose with a first solvent and sodium periodate and then performing oxidation reaction to obtain oxidized cellulose; and mixing the oxidized cellulose with a second solvent and an amino cationic antibacterial agent and then performing grafting reaction to obtain modified cellulose. The present invention uses an ionic liquid co-solvent to dissolve and regenerate cellulose for pretreatment. The cations in the ionic liquid prevent the interaction between cellulose molecules, promote the dissolution of cellulose, and successfully break the hydrogen bonds between cellulose molecules and within the molecule, thereby causing the structural rearrangement of cellulose in terms of crystal structure and surface morphology, improving the ability of cellulose to be oxidized, and reducing the time required for cellulose oxidation; then sodium periodate is used to oxidize the hydroxyl group of the cellulose glucose unit to an aldehyde group, and a Schiff base reaction occurs with an amino cationic antibacterial agent, and the antibacterial group is successfully grafted, so that the modified cellulose has a strong antibacterial property; after the regenerated cellulose is selectively oxidized by sodium periodate and grafted with an amino cationic antibacterial agent, its hydrogen bond structure is destroyed, greatly reducing the glass transition temperature of the cellulose material, so that the modified cellulose material has thermoplasticity, and can even achieve plastic processing without adding plasticizers and thermoplastics. Experimental results show that the glass transition temperature of the modified cellulose prepared by the present invention has been greatly reduced, and plastic processing can be performed at 200°C, and it has good antibacterial activity against Escherichia coli and Staphylococcus aureus, and has a strong antibacterial property. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a reaction principle diagram of cellulose modification in the present invention;

[0023] Figure 2 Graph showing the aldehyde content of the oxidized cellulose prepared in Examples 1 and 2 of the present invention and Comparative Example 1;

[0024] Figure 3 The infrared spectra of the oxidized cellulose, modified cellulose, polyhexamethyleneguanidine hydrochloride raw materials and pulp cellulose raw materials prepared in Example 1 of the present invention;

[0025] Figure 4 The infrared spectra of the oxidized cellulose, modified cellulose, polyhexamethyleneguanidine hydrochloride raw materials and pulp cellulose raw materials prepared in Example 2 of the present invention;

[0026] Figure 5 The TGA curves of the modified cellulose and pulp cellulose raw materials prepared in Examples 1 and 2 of the present invention;

[0027] Figure 6 DTG curves of modified cellulose and pulp cellulose raw materials prepared in Examples 1 and 2 of the present invention;

[0028] Figure 7 DSC curves of modified cellulose and pulp cellulose raw materials prepared in Examples 1 and 2 of the present invention;

[0029] Figure 8 The images are of the pulp cellulose raw materials of the present invention and the modified cellulose prepared in Examples 1, 2 and Comparative Example 1 after being pressed into sheets by a flat vulcanizing machine at 200°C;

[0030] Fig. 9 The rheological temperature scanning curve of the modified cellulose prepared in Example 1 of the present invention at 180-250°C;

[0031] Fig.10 The rheological temperature scanning curve of the modified cellulose prepared in Example 2 of the present invention at 180-250°C;

[0032] Fig.11 The antibacterial ring diagrams of Escherichia coli and Staphylococcus aureus of the modified cellulose prepared in Example 1 of the present invention and Comparative Example 2 are shown. DETAILED DESCRIPTION

[0033] The present invention provides a method for preparing modified cellulose, comprising the following steps:

[0034] (1) mixing pulp cellulose and ionic liquid co-solvent and then pretreating them to obtain regenerated cellulose;

[0035] (2) mixing the regenerated cellulose obtained in step (1) with a first solvent and sodium periodate and subjecting the mixture to an oxidation reaction to obtain oxidized cellulose;

[0036] (3) The oxidized cellulose obtained in step (2) is mixed with a second solvent and an amino cationic antibacterial agent and then subjected to a grafting reaction to obtain modified cellulose.

[0037] The present invention has no particular limitation on the sources of all raw materials, and commercially available ones can be used.

[0038] The invention mixes pulp cellulose and ionic liquid co-solvent and then performs pretreatment to obtain regenerated cellulose.

[0039] In the present invention, the pulp cellulose is preferably a complex mixture of cellulose and other lignins. The present invention has no requirements on the specific type of cellulose in the pulp cellulose, and commercially available cellulose may be used.

[0040] In the present invention, the ionic liquid co-solvent preferably includes an ionic liquid and dimethyl sulfoxide, and the mass ratio of the ionic liquid to dimethyl sulfoxide is preferably (70-90):(10-30), further preferably (75-85):(15-25), and more preferably 80:20. Compared with other solvents (such as N,N-dimethylformamide, etc.), dimethyl sulfoxide has a better effect on dissolving pulp cellulose. Adding the co-solvent dimethyl sulfoxide (DMSO) will reduce the viscosity of the solution, which is beneficial to the dissolution and precipitation of regenerated cellulose. The mass ratio of the above ionic liquid to dimethyl sulfoxide can make the pretreatment reaction more complete.

[0041] In the present invention, the ionic liquid is preferably one or more of 1-ethyl-3-methylimidazolium acetate, 1-allyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium chloride and N,N-dimethylimidazolium acetate; as an embodiment of the present invention, the ionic liquid can be 1-ethyl-3-methylimidazolium acetate. The above-mentioned types of ionic liquids can successfully break the hydrogen bonds between and within cellulose molecules through the action of ionic liquid co-solvents on pulp cellulose, thereby causing structural rearrangement of cellulose in terms of crystal structure and surface morphology, which is beneficial to further improve the efficiency of subsequent modification of cellulose.

[0042] In the present invention, the mixing of pulp cellulose and ionic liquid co-solvent is preferably adding pulp cellulose into the ionic liquid co-solvent.

[0043] In the present invention, the mass ratio of pulp cellulose to ionic liquid co-solvent is preferably (1-3):25, more preferably 1:25. The mass ratio of pulp cellulose to ionic liquid co-solvent can make cellulose more fully dissolved and regenerated in the ionic liquid solvent.

[0044] In the present invention, the pretreatment temperature is preferably 50-90°C, more preferably 70-90°C, and more preferably 90°C; the pretreatment time is preferably 1-2h, more preferably 1-1.5h, and more preferably 1h. In the present invention, during the pretreatment process, the anions of the ionic liquid form strong hydrogen bonds with the hydroxyl hydrogen atoms on the cellulose chain, thereby destroying the hydrogen bond network between the cellulose molecules and fully dissolving the cellulose molecules; in addition, the cations in the ionic liquid interact with the hydroxyl oxygen atoms of the cellulose through non-bonding or π electron interactions, preventing the interaction between the cellulose molecules and further promoting the dissolution of cellulose; the dissolution of cellulose by the ionic liquid co-solvent will successfully break the hydrogen bonds between the cellulose molecules and within the molecules, thereby causing the structural rearrangement of the cellulose in terms of crystal structure and surface morphology, thereby affecting the efficiency of the subsequent modification of cellulose, that is, improving the oxidation ability of sodium periodate on cellulose.

[0045] In the present invention, the pretreatment is preferably carried out under stirring conditions. The present invention has no particular limitation on the stirring rate, and any rate known to those skilled in the art can be used to promote dispersion.

[0046] After the pretreatment is completed, the present invention preferably mixes the mixed solution obtained by the pretreatment with water and separates the solid and liquid to obtain regenerated cellulose. The present invention reduces the solubility of the regenerated cellulose in the ionic liquid by adding water to promote the precipitation of the regenerated cellulose.

[0047] In the present invention, the mixing of the mixed solution and water is preferably performed by squeezing the mixed solution obtained by the pretreatment into water for stirring; the water is preferably deionized water, and the temperature of the deionized water is preferably 40-80°C, more preferably 60°C.

[0048] As an embodiment of the present invention, the solid-liquid separation can be filtration; after the filtration, the obtained solid can be washed. The present invention has no special limitation on the filtration and washing operations, and methods well known to those skilled in the art can be used.

[0049] After obtaining the regenerated cellulose, the present invention mixes the regenerated cellulose with a first solvent and sodium periodate and then performs an oxidation reaction to obtain oxidized cellulose.

[0050] In the present invention, the first solvent is preferably a mixed solvent of isopropanol and water, and the volume ratio of isopropanol to water is preferably (0.06-0.12):1, more preferably 0.06-0.10:1, and more preferably 0.063:1. The mixed solvent of isopropanol and water at the above volume ratio can make the contact between sodium periodate and cellulose more complete, thereby improving the rate and efficiency of the oxidation reaction.

[0051] In the present invention, the mixing of the regenerated cellulose, the first solvent and sodium periodate is preferably performed by adding the regenerated cellulose into the first solvent and then adding sodium periodate.

[0052] As an embodiment of the present invention, the volume ratio of the mass of the regenerated cellulose to the first solvent can be 4 to 20 g / L, 6 to 16 g / L, or 8 to 12 g / L.

[0053] As an embodiment of the present invention, the mass ratio of the regenerated cellulose to sodium periodate can be 1:1.4-5.4, or 1:2-4.8, or 1:3-4.

[0054] In the present invention, the oxidation reaction is preferably carried out in the dark; as an embodiment of the present invention, the temperature of the oxidation reaction can be 25-50°C, 27-45°C, or 30-40°C; the time of the oxidation reaction is preferably 0.5-6h, as an embodiment of the present invention, the time of the oxidation reaction can be 1-5h, or 2-4h. During the oxidation reaction, the hydroxyl groups of the glucose units of the cellulose are oxidized to aldehyde groups. By controlling the conditions of the oxidation reaction, the hydroxyl groups in the regenerated cellulose can be fully oxidized to aldehyde groups, thereby increasing the aldehyde content of the oxidized cellulose.

[0055] After the oxidation reaction is completed, the product of the oxidation reaction is preferably washed and filtered in sequence to obtain oxidized cellulose. The present invention has no particular limitation on the washing and filtering operations, and the excess water-soluble substances can be removed in a manner well known to those skilled in the art.

[0056] After obtaining the oxidized cellulose, the present invention mixes the oxidized cellulose with a second solvent and an amino cationic antimicrobial agent and then performs a grafting reaction to obtain modified cellulose.

[0057] In the present invention, the second solvent is preferably an alkali solution with a pH value of 10 to 11. As an embodiment of the present invention, the alkali solution can be a sodium hydroxide solution with a pH value of 10 or a sodium hydroxide solution with a pH value of 11.

[0058] In the present invention, the amino cationic antibacterial agent is preferably one or more of polyhexamethyleneguanidine hydrochloride, polyhexamethylene biguanidine hydrochloride and quaternary ammonium salt, more preferably polyhexamethyleneguanidine hydrochloride.

[0059] As an embodiment of the present invention, the mass ratio of the oxidized cellulose to the amino cationic antimicrobial agent can be 1:0.1-1.4, 1:0.5-1.0, or 1:0.6-0.8. At the above mass ratio, the Schiff base grafting reaction can be fully carried out.

[0060] In the present invention, the mixing of the oxidized cellulose, the second solvent and the amino cationic antibacterial agent is preferably performed by adding the oxidized cellulose into the second solvent and then adding the amino cationic antibacterial agent.

[0061] As an embodiment of the present invention, the volume ratio of the mass of the oxidized cellulose to the second solvent may be 4 to 20 g / L, 8 to 15 g / L, or 9 to 10 g / L.

[0062] In the present invention, the pH value of the grafting reaction is preferably 10-11; as an embodiment of the present invention, the pH value of the grafting reaction can be 10 or 11. In the present invention, the pH value of the grafting reaction is preferably ensured to be within the above range by adding sodium hydroxide solution during the grafting reaction. In an embodiment of the present invention, the concentration of the sodium hydroxide solution is 0.01M.

[0063] As an embodiment of the present invention, the temperature of the grafting reaction can be 25-50°C, 30-50°C, or 40-50°C; as an embodiment of the present invention, the time of the grafting reaction can be 1-6h, or 3-5h.

[0064] After the grafting reaction is completed, the product of the grafting reaction is preferably washed, filtered and dried in sequence to obtain modified cellulose. The present invention has no particular limitation on the washing, filtering and drying operations, and the solvent can be removed by a method well known to those skilled in the art.

[0065] In the present invention, the modification principle of cellulose is as follows Figure 1 As shown, cellulose is oxidized with sodium periodate at 50°C in the dark to oxidize the hydroxyl groups to aldehyde groups to obtain oxidized cellulose; oxidized cellulose is grafted with polyhexamethyleneguanidine hydrochloride at 50°C by Schiff base to obtain modified cellulose.

[0066] The present invention also provides modified cellulose prepared by the preparation method described in the above technical solution.

[0067] The present invention also provides a modified cellulose composite material, which comprises the following components, measured by weight: 50 to 100 parts of modified cellulose, 0 to 10 parts of plasticizer, 0 to 50 parts of degradable synthetic polymer and 0.1 to 0.3 parts of antioxidant; the modified cellulose is the modified cellulose described in the above technical solution.

[0068] In the present invention, based on 50 to 100 parts by mass of the modified cellulose, the modified cellulose composite material preferably includes 0 to 10 parts of a plasticizer, and more preferably 0 parts. The present invention can achieve plastic processing without adding a plasticizer and a thermoplastic, and does not cause the problem of poor stability of the composite thermoplastic material caused by adding an ionic liquid plasticizer.

[0069] In the present invention, the plasticizer is preferably one or more of water, polyethylene glycol (molecular weight less than 500), triacetin, epoxidized soybean oil and polyethylene glycol diglycidyl ether, more preferably water.

[0070] In the present invention, based on 50 to 100 parts by mass of the modified cellulose, the modified cellulose composite material preferably includes 0 to 50 parts of the degradable synthetic polymer, and more preferably 50 parts. The present invention improves the tensile strength and elongation at break of the modified cellulose composite material by adding the degradable synthetic polymer to the modified cellulose composite material.

[0071] In the present invention, the degradable synthetic polymer is preferably one or more of polylactic acid (PLA), polybutylene adipate / terephthalate (PBAT), polybutylene succinate (PBS), poly(ε-caprolactone) (PCL), more preferably polybutylene adipate / terephthalate (PBAT).

[0072] In the present invention, based on 50 to 100 parts by mass of the modified cellulose, the modified cellulose composite material preferably includes 0.1 to 0.3 parts by mass of the antioxidant, and more preferably 0.2 parts by mass.

[0073] In the present invention, the antioxidant is preferably one or more of antioxidant 1010, antioxidant 1076, and 2,6-di-tert-butylphenol (BHT), and antioxidant 1010 is more preferred.

[0074] As an embodiment of the present invention, the components of the modified cellulose composite material may be composed of 49.9-89.82 parts of modified cellulose, 9.98-49.9 parts of degradable synthetic polymer and 0.2 parts of antioxidant in terms of mass fractions.

[0075] The modified cellulose composite material provided by the present invention has a tensile strength of up to 20.17 MPa and an elongation at break of up to 17.25%, which can meet the mechanical property requirements of different products for a modified cellulose composite material that can be thermoplastically processed and has antibacterial properties.

[0076] In the present invention, the method for preparing the modified cellulose composite material preferably comprises the following steps:

[0077] The modified cellulose, the plasticizer, the degradable synthetic polymer and the antioxidant are placed in a high-speed mixer and stirred to obtain a mixture;

[0078] The mixture is melt-extruded and granulated using a twin-screw extruder to obtain a modified cellulose composite material.

[0079] In the present invention, the rotation speed of the high-speed stirrer is preferably 1000-2000 rpm, more preferably 2000 rpm; the stirring time is preferably 10-20 min, more preferably 15 min; the present invention has no special limitation on the stirring temperature, which can be room temperature.

[0080] In the present invention, the temperature of the twin-screw extruder for melt extrusion granulation is preferably 120-180°C, more preferably 180°C.

[0081] In the present invention, the modified cellulose composite material can be processed by an injection molding machine, a casting machine, a melt spinning machine and other equipment to prepare products of various shapes.

[0082] In order to further illustrate the present invention, the modified cellulose and the preparation method thereof and the modified cellulose composite material provided by the present invention are described in detail below in conjunction with the examples, but they should not be construed as limiting the scope of protection of the present invention.

[0083] The raw materials and manufacturers used in the embodiments of the present invention are as follows:

[0084] Pulp cellulose was purchased from Shandong Zhongke Henglian Bio-based Materials Co., Ltd., isopropanol was purchased from Tianjin Tianli Chemical Reagent Co., Ltd., sodium periodate was purchased from Shanghai Myrrel Chemical Technology Co., Ltd., polyhexamethyleneguanidine hydrochloride was purchased from Hebei Jinhong Chemical Co., Ltd., sodium hydroxide was purchased from Tianjin Damao Chemical Reagent Factory, hydroxylamine chloride was purchased from Shanghai Bide Pharmaceutical Technology Co., Ltd., 1-ethyl-3-methylimidazole acetate was purchased from Zhejiang Lande Energy Technology Development Co., Ltd., dimethyl sulfoxide was purchased from Shanghai Myrrel Chemical Technology Co., Ltd., antioxidant 1010 was purchased from BASF AG, and polybutylene adipate / terephthalate (PBAT) was purchased from Jinhui Zhaolong High-tech Technology Co., Ltd.

[0085] Example 1

[0086] 1) Add 4 g of pulp cellulose to 100 g of 1-ethyl-3-methylimidazolium acetate / dimethyl sulfoxide co-solvent (the mass ratio of 1-ethyl-3-methylimidazolium acetate to dimethyl sulfoxide is 80 / 20), stir at 90° C. for 1 h to obtain a cellulose solution, then squeeze the solution into deionized water at 60° C. and stir to completely separate the co-solvent from the cellulose, filter, and wash to obtain regenerated cellulose.

[0087] 2) Add 2 g of regenerated cellulose to 500 mL of isopropanol aqueous solution (the volume ratio of isopropanol to water is 0.063), and then add 10.8 g of sodium periodate to carry out oxidation reaction in a dark environment. The reaction temperature is room temperature; the time is: 6 hours. After the reaction is completed, wash thoroughly with water and filter to remove excess water-soluble substances to obtain oxidized cellulose.

[0088] 3) 2 g of oxidized cellulose was added to 500 mL of alkaline solution with a pH of 10, and then 1 g of polyhexamethyleneguanidine hydrochloride was added at 50°C to react with the oxidized cellulose to undergo a Schiff base reaction. During the reaction, 0.01 M sodium hydroxide solution was added dropwise to adjust the pH of the reaction system to 10 to accelerate the Schiff base reaction. After the reaction was completed for 6 h, the modified cellulose was washed, filtered, and dried to obtain the modified cellulose.

[0089] Example 2

[0090] The difference between Example 2 and Example 1 is that step 2) is different:

[0091] 2) Disperse 2 g of regenerated cellulose in 100 mL of isopropanol aqueous solution (the volume ratio of isopropanol to water is 0.063), then add 2.8 g of sodium periodate to carry out oxidation reaction in a dark environment. The reaction temperature is 50°C; the time is: 0.5 h. After the reaction is completed, wash thoroughly with water and filter to remove excess water-soluble substances to obtain oxidized cellulose.

[0092] Embodiments 3 to 5

[0093] The composition and proportion of the modified cellulose composite materials in Examples 3, 4 and 5 are shown in Table 1. The specific preparation methods are as follows:

[0094] 1) The modified cellulose obtained in Example 1, polybutylene adipate / terephthalate (PBAT) and antioxidant 1010 were placed in a high-speed stirrer and stirred at room temperature at a speed of 2000 rpm for 15 min.

[0095] 2) The uniformly stirred mixture was melt-extruded and granulated using a twin-screw extruder at 180° C. to obtain a modified cellulose composite material.

[0096] Table 1. Composition and ratio of modified cellulose composite materials in Examples 3 to 5

[0097] Product Name Modified cellulose (wt.%) PBAT (wt.%) Antioxidant 1010 (wt.%) Example 3 89.82 9.98 0.2 Example 4 69.86 29.94 0.2 Example 5 49.9 49.9 0.2

[0098] The tensile test was performed on the tensile specimens obtained by injection molding the modified cellulose of Example 1 and the cellulose composite materials of Examples 3, 4, and 5. The test method is: the tensile test was performed on the tensile specimens at room temperature according to GB / T1040.1-2018. The mechanical property test results are shown in Table 2 below.

[0099] Table 2. Mechanical properties of modified cellulose composites in Examples 3 to 5

[0100] sample Tensile strength(MPa) Elongation at break (%) Example 1 13.17 0.18 Example 3 14.24 5.57 Example 4 17.33 13.75 Example 5 20.17 17.25

[0101] Comparative Example 1

[0102] The difference between Comparative Example 1 and Example 1 is that step 1) is not included, and the regenerated cellulose in step 2) is replaced by pulp cellulose.

[0103] Comparative Example 2

[0104] The difference between Comparative Example 1 and Example 1 is that step 3) is different:

[0105] 3) 2 g of oxidized cellulose was added to 500 mL of deionized water, and then 1 g of sodium borohydride was added at room temperature to reduce the oxidized cellulose. In addition, sodium dihydrogen phosphate was added to 0.01 M to limit the alkaline degradation of dialdehyde cellulose caused by the increase in pH due to the addition of sodium borohydride. After 4 h of reaction, the modified cellulose was washed, filtered, and dried to obtain the modified cellulose.

[0106] Test aldehyde content

[0107] The aldehyde content of the oxidized cellulose obtained by the treatment in step 2) in Examples 1 and 2 and Comparative Example 1 is shown in FIG. Figure 2 , the specific test method is as follows:

[0108] 1) Measure 25 mL of 0.25 mol / L hydroxylamine chloride (NH2OH·HCl) and add it to a 50 mL beaker. Then use 0.1 mol / L sodium hydroxide (NaOH) solution to adjust its pH to 4.0 (the volume of added NaOH is negligible).

[0109] 2) Add about 100 mg of the completely dried oxidized sample to the solution prepared in step 1) and stir at room temperature for 4 h.

[0110] 3) After the reaction in step 2) is completed, the pH of the reaction mixture is re-titrated to 4.0 using 0.1 mol / L NaOH solution.

[0111] In step 2), a blank control group was set up, and unoxidized pulp cellulose was added to NH2OH·HCl solution, stirred at room temperature for 4 hours, and then titrated with 0.1 mol / L NaOH solution. Each titration reaction was carried out three independent parallel experiments, and the results were averaged. The AC of the oxidized sample was calculated according to the following formula:

[0112] AC=(V NaOH(氧化) -V NaOH(空白) )×C NaOH / m o ;

[0113] Where V NaOH(氧化) and V NaOH(空白) are the volumes of NaOH solution required to titrate the oxidized sample and pulp cellulose to pH = 4.0, C NaOHis the concentration of NaOH solution, m o is the dry weight of the oxidized sample.

[0114] Test infrared spectrum

[0115] An INVENIO-S Fourier transform infrared spectrometer (Guangzhou Taoyi Trading Co., Ltd.) was used to record the wavelength range of 4000-500 cm-1 in the KBr pellet transmission mode. -1 FTIR spectrum in the range, with a cumulative scan number of 32 and a resolution of 4 cm -1 .

[0116] The infrared spectra of the oxidized cellulose, modified cellulose, polyhexamethyleneguanidine hydrochloride raw materials and pulp cellulose raw materials prepared in Example 1 are shown in Figure 3 ;

[0117] The infrared spectra of the oxidized cellulose, modified cellulose, polyhexamethyleneguanidine hydrochloride raw materials and pulp cellulose raw materials prepared in Example 2 are shown in FIG. Figure 4 .

[0118] Test TGA curve and DTG curve

[0119] 5-10 mg of sample was placed in a ceramic crucible and thermogravimetric analysis was performed using a TGA2 thermogravimetric analyzer under N2 atmosphere at a flow rate of 50 mL / min. The test temperature range was 30-700°C and the heating rate was 10°C / min.

[0120] The TGA curves of the modified cellulose and pulp cellulose raw materials prepared in Examples 1 and 2 are shown in Figure 5 .

[0121] The DTG curves of the modified cellulose and pulp cellulose raw materials prepared in Examples 1 and 2 are shown in Figure 6 .

[0122] Test DSC curve

[0123] The samples were tested using a DSC204FI DSC differential scanning calorimeter with a heating range of 0°C to 200°C and a heating rate of 10°C / min. After maintaining the constant temperature for 2 minutes, the temperature was lowered to 30°C at a cooling rate of 10°C / min.

[0124] The DSC curves of the modified cellulose and pulp cellulose raw materials prepared in Examples 1 and 2 are shown in Figure 7 .

[0125] Test the image after being pressed by a flat vulcanizing machine

[0126] The images of the pulp cellulose raw material and the modified cellulose prepared in Examples 1, 2 and Comparative Example 1 after being pressed into sheets by a flat vulcanizer at 200°C are shown in FIG. Figure 8.

[0127] Test the rheological temperature scanning curve at 180-250℃

[0128] The rheological temperature scanning curve of the modified cellulose prepared in Example 1 at 180-250°C is shown in FIG. Fig. 9 ;

[0129] The rheological temperature scanning curve of the modified cellulose prepared in Example 2 at 180-250°C is shown in FIG. Fig.10 .

[0130] Testing the antibacterial properties of modified cellulose

[0131] (1) Preparation of culture medium: Dissolve 40 g of solid nutrient agar culture medium in 1 L of boiling water, place in a conical flask, and seal the flask mouth with a breathable sealing film. Sterilize in an autoclave at 121°C, 0.1 MPa for 30 min and cool to about 50°C. Pour 20 mL of sterile culture medium into a culture dish, place under ultraviolet light for sterilization, and wait for solidification for use.

[0132] (2) Preservation of bacterial strains: Inoculate the bacterial strains on a slant of nutrient agar medium and culture them in a biochemical incubator at (37±1)°C and store them in a medical refrigerator at 0-5°C.

[0133] (3) Activation of bacterial strains: Before the experiment, the preserved bacteria were inoculated on a slant of NA culture medium and cultured in a biochemical incubator for 24 h.

[0134] (4) Preparation of bacterial suspension: Use an inoculation gun to gently scrape 1-2 loops of freshly inoculated bacteria and add them to 20 mL of physiological saline sterilized in an autoclave to prepare a bacterial solution. Dilute the bacterial solution in a 10-fold concentration gradient. First, add 9 mL of sterile water to several conical flasks, take 1 mL of the bacterial solution to the first conical flask, shake well, and draw 1 mL of the bacterial solution from the first conical flask to the second conical flask. Dilute it step by step to prepare bacterial suspensions with different concentration gradients. Take 100 μL of the bacterial suspension in each conical flask and drop it onto the agar medium. Use a spreading stick to spread the bacteria evenly. Seal it with plastic wrap and place it in an incubator for 48 hours. Observe the cultured bacteria and select the lowest bacterial suspension concentration that can evenly cover the surface of the culture medium as the bacterial suspension concentration for the antibacterial experiment.

[0135] (5) Analysis by the inhibition zone method: Prepare 4 solid agar culture media for use, then take 100 μL of the diluted bacterial solution and drip it onto the wells of the solid agar culture media in turn, then take a coating rod and roast it for 15 to 20 seconds. After it is fully disinfected, use it to evenly spread the bacterial solution on the culture media. Cut a modified cellulose sample with a diameter of 8 mm, place the sample in the middle of the culture media, and then place it in an incubator for 24 hours to observe the size of the inhibition zone.

[0136] The inhibition ring diagrams of Escherichia coli and Staphylococcus aureus of the modified cellulose prepared in Example 1 of the present invention and Comparative Example 2 are shown in FIG. Fig.11 .

[0137] from Figure 2 It can be seen that the aldehyde content of the oxidized cellulose prepared in Example 1 is 4.22 mmol / g, the aldehyde content of the oxidized cellulose prepared in Example 2 is 4.12 mmol / g, and the aldehyde content of the oxidized cellulose prepared in Comparative Example 1 is 1.74 mmol / g. The aldehyde content of the oxidized cellulose in Example 1 is increased by 143% compared with that in Comparative Example 1. Compared with Comparative Example 1, the oxidized cellulose obtained in Examples 1 and 2 has a higher aldehyde content and a deeper oxidation degree at the same time (6 h). It can be seen that the dissolution and regeneration of pulp cellulose by ionic liquid co-solvent can significantly improve the modification degree of the material and shorten the reaction time.

[0138] from Figure 3 and Figure 4 From the infrared spectra of oxidized cellulose, modified cellulose, polyhexamethyleneguanidine hydrochloride raw materials and pulp cellulose raw materials prepared in Examples 1 and 2, it can be seen that aldehyde groups (C=O) appear in the regenerated cellulose after the oxidation reaction, indicating that the oxidation reaction is successful to oxidize the hydroxyl groups of the cellulose glucose unit to aldehyde groups. After the reaction of 1,6-hexanediamine Schiff base, the stretching vibration absorption peak of the aldehyde group completely disappears, and the characteristic peaks of the imine bond (C=N) and the carbon-hydrogen bond (-CH2-) on the alkyl chain appear. In addition, at 500-750cm -1 The infrared spectrum curve in the range of 1000 nm becomes flat, which indicates that the D-pyranose ring is broken by ring opening. Figure 1 The principle was oxidation and Schiff base modification. (1657cm -1 The stretching vibration absorption peak of the imine bond (C=N) is 1730 cm -1 The stretching vibration peak of aldehyde group (C=O) is 2904cm -1 The peak at 2852 cm is the stretching vibration peak of the carbon-hydrogen bond (CH) on the cellulose chain. -1 and 2927cm -1 The peaks at 500-750cm are the stretching vibration peaks of the carbon-hydrogen bond (-CH2-) on the alkyl chain and -1 The peak at the center is the stretching vibration peak of the D-pyranose ring.

[0139] from Figure 5 It can be seen from the TGA curve that the residual mass of the modified cellulose prepared in Examples 1 and 2 after degradation is significantly higher than that of the pulp cellulose raw material, indicating that Examples 1 and 2 are successfully grafted with polyhexamethylene guanidine hydrochloride after Schiff base reaction.

[0140] from Figure 6 It can be seen from the DTG curve that the peak temperature of the modified cellulose prepared in Examples 1 and 2 is significantly lower than the peak temperature of the pulp cellulose raw material, which indicates that the structure of Examples 1 and 2 becomes loose after modification, which provides convenience for the next step of thermoplastic processing.

[0141] from Figure 7 It can be seen from the DSC curve that pure cellulose does not have a glass transition temperature, but the modified cellulose prepared in Examples 1 and 2 after modification has an obvious glass transition temperature. This is because after modification, Examples 1 and 2 destroy the hydroxyl groups on the cellulose chain, thereby destroying the hydrogen bond network between the chains, so the glass transition temperature of Examples 1 and 2 has dropped significantly.

[0142] from Figure 8 It can be seen that the pulp fiber cannot be plastic processed at 200°C, while the modified cellulose prepared in Examples 1 and 2 can be plastic processed at 200°C. Compared with Comparative Example 1, Example 1 has melt processing conditions after modification while Comparative Example 1 does not, indicating that within the same modification time, the cellulose material regenerated by the ionic liquid co-solvent has a stronger degree of modification.

[0143] from Fig. 9 and Fig.10 It can be seen from the rheological temperature scanning curves of the modified cellulose prepared in Examples 1 and 2 that the storage modulus (G') of the material remains higher than the loss modulus (G") in a wide temperature range, which indicates that the prepared material has good stability. At 240-250°C, the loss modulus (G") of the material is higher than its storage modulus (G'), which indicates that the prepared material is transformed from the original viscoelastic solid material to a viscous fluid material at this temperature, which also shows that the cellulose materials prepared in Examples 1 and 2 can melt and flow at high temperatures and have material properties that can be thermoplastically processed.

[0144] from Fig.11 It can be seen that the modified cellulose prepared in Comparative Example 2 had no antibacterial rings in both Escherichia coli and Staphylococcus aureus culture dishes, but the modified cellulose prepared in Example 1 showed obvious antibacterial rings in both culture dishes, which indicates that the material has strong antibacterial properties after grafting with cationic amino antibacterial agents, and has good antibacterial activity against Escherichia coli and Staphylococcus aureus.

[0145] It can be seen from the above embodiments and comparative examples that the modified cellulose prepared by the present invention has a significant decrease in glass transition temperature, can be plastic processed at 200°C, has good antibacterial activity against Escherichia coli and Staphylococcus aureus, and has strong antibacterial properties.

[0146] Without adding plasticizer, the tensile strength and elongation at break of the modified cellulose composite material prepared with modified cellulose, degradable synthetic polymer and antioxidant as raw materials are improved compared with the modified cellulose material. Adjusting the ratio of modified cellulose and degradable synthetic polymer can meet the mechanical properties requirements of different products for modified cellulose composite materials.

[0147] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing modified cellulose, comprising the following steps: (1) mixing pulp cellulose and an ionic liquid co-solvent and then pretreating the mixture to obtain regenerated cellulose; (2) mixing the regenerated cellulose obtained in step (1) with a first solvent and sodium periodate and subjecting the mixture to an oxidation reaction to obtain oxidized cellulose; (3) The oxidized cellulose obtained in step (2) is mixed with a second solvent and an amino cationic antibacterial agent and then subjected to a grafting reaction to obtain modified cellulose.

2. The preparation method according to claim 1, characterized in that: The pretreatment temperature in step (1) is 50-90° C., and the pretreatment time is 1-2 hours.

3. The preparation method according to claim 1, characterized in that: In the step (1), the ionic liquid co-solvent comprises an ionic liquid and dimethyl sulfoxide, and the mass ratio of the ionic liquid to dimethyl sulfoxide is (70-90):(10-30).

4. The preparation method according to claim 3, characterized in that: The ionic liquid is one or more of 1-ethyl-3-methylimidazolium acetate, 1-allyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium chloride and N,N-dimethylimidazolium acetate.

5. The preparation method according to any one of claims 1 to 4, characterized in that: After the pretreatment in step (1) is completed, the mixed liquid obtained by the pretreatment is mixed with water and then solid-liquid separation is performed to obtain regenerated cellulose.

6. The preparation method according to claim 1, characterized in that: In the step (2), the first solvent is a mixed solvent of isopropanol and water, and the volume ratio of isopropanol to water is (0.06-0.12):

1.

7. The preparation method according to claim 1, characterized in that: The pH value of the grafting reaction in step (3) is 10-11.

8. The preparation method according to claim 1, characterized in that: In the step (3), the amino cationic antibacterial agent is one or more of polyhexamethyleneguanidine hydrochloride, polyhexamethylene biguanide hydrochloride and quaternary ammonium salt.

9. Modified cellulose prepared by the preparation method according to any one of claims 1 to 8.

10. A modified cellulose composite material, comprising the following components, by weight: 50-100 parts of modified cellulose, 0-10 parts of plasticizer, 0-50 parts of degradable synthetic polymer and 0.1-0.3 parts of antioxidant, wherein the modified cellulose is the modified cellulose according to claim 9.

Citation Information

Patent Citations

  • Preparation method of cellulose-based antibacterial material dialdehyde cellulose-lysine

    CN107746433A

  • Tea leaf residue modified oxidized cellulose composite film, and preparation method and application thereof

    CN109293959A

  • Antibacterial finishing method of cellulose fabric

    CN109457468A

  • Preparation method of oxidized cellulose with high substitution degree

    CN110330569A

  • Aminated modified bacterial cellulose antibacterial film material and preparation method thereof

    CN117164925A

Cited By

  • High-performance regenerated fiber and composite preparation process thereof

    CN120844222A